2020
DOI: 10.1200/jco.2020.38.15_suppl.e21110
|View full text |Cite
|
Sign up to set email alerts
|

Atezolizumab and platinum-based chemotherapy in extensive-stage small cell lung cancer: A single center experience.

Abstract: e21110 Background: In extensive stage small-cell lung cancer (ES-SCLC) immune check-point inhibitors, atezolizumab and durvalumab, when combined with chemotherapy in the first-line setting show better efficacy than chemotherapy alone with safety profile similar as the adverse events of individual agents. Methods: We administered atezolizumab, etoposide and platinum, either carboplatin or cisplatin, in the first-line treatment in 24 newly diagnosed patients with ES-SCLC. Patients were treated until disease pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…At 18 months, survival was 34.0% and 21.0%, respectively [ 14 ]. Real-world clinical practice studies also confirmed the benefit of atezolizumab and chemotherapy in the first-line treatment of ES-SCLC [ 15 ]. Based on the phase 3 CASPIAN RCT results, durvalumab was approved in the first-line treatment of ES-SCLC [ 13 ].…”
Section: Discussionmentioning
confidence: 91%
“…At 18 months, survival was 34.0% and 21.0%, respectively [ 14 ]. Real-world clinical practice studies also confirmed the benefit of atezolizumab and chemotherapy in the first-line treatment of ES-SCLC [ 15 ]. Based on the phase 3 CASPIAN RCT results, durvalumab was approved in the first-line treatment of ES-SCLC [ 13 ].…”
Section: Discussionmentioning
confidence: 91%